A phase III, randomized, clinical, crossover study to evaluate the non-inferiority of an ophthalmic solution of preservative-free latanoprost at 0.005% in patients with primary open-angle glaucoma. Issue 3 (2018) - Sánchez-Castellanos, Victoria E; Olvera-Montaño, Oscar; Paczka, José A
No abstract available